2014
DOI: 10.1136/bjophthalmol-2014-305150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new optical biometry device for measurements of ocular components and its comparison with IOLMaster

Abstract: The repeatability and reproducibility of AL-Scan was excellent for all parameters, except WTW and PD. Excluding WTW, good agreement was found between the AL-Scan and IOLMaster. The 2.4-mm diameter K value may be the most reliable choice for calculation of IOL power with the AL-Scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 25 publications
10
52
3
2
Order By: Relevance
“…Bu biyometriler, nonkontakt olmasının yanında MKK, ÖKD, lens kalınlığı, AU, keratometrik değerlerin ölçümüne de olanak sağlamaktadır. 7,[13][14][15][16] Yeni geliştirilen optik biyometri ölçümleri ile uzun yıllardır altın standart olarak kullandığımız ultra sonik biyometri ölçümleri arasındaki uyumluluk ve farklılıkların bilinmesi önemlidir. Çünkü AU hesaplanırken yapılacak 0,01 mm hata, 0,03 D GİL gücü farklılığına neden olmaktadır.…”
Section: Discussionunclassified
“…Bu biyometriler, nonkontakt olmasının yanında MKK, ÖKD, lens kalınlığı, AU, keratometrik değerlerin ölçümüne de olanak sağlamaktadır. 7,[13][14][15][16] Yeni geliştirilen optik biyometri ölçümleri ile uzun yıllardır altın standart olarak kullandığımız ultra sonik biyometri ölçümleri arasındaki uyumluluk ve farklılıkların bilinmesi önemlidir. Çünkü AU hesaplanırken yapılacak 0,01 mm hata, 0,03 D GİL gücü farklılığına neden olmaktadır.…”
Section: Discussionunclassified
“…Optical biometry is a rapid, easy to use and non-contact method to assess the eye's biometry and calculate the IOL power, so the method is preferred by many ophthalmologists [12][13][14]. Recently, the AL-Scan optical biometer has been introduced into clinical practice, and has shown good agreement with the common optical biometer, IOL Master [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The IOL Master is currently considered the gold standard biometer for AL measurements, showing good repeatability and accuracy [19]. Huang et al [15] demonstrated that the AL measurements of the AL-Scan and IOL Master were very close to each other, with 95% of the readings within -0.12 to 0.1 mm. The authors also found the K value comparable between the two devices.…”
Section: Medicine Science 2016;5(1):222-32 Repeatability and Reproducmentioning
confidence: 99%
See 2 more Smart Citations